Acute Recanalization of Thrombo-Embolic Ischemic Stroke with pREset (ARTESp): the impact of occlusion time on clinical outcome of directly admitted and transferred patients. (16th August 2016) - Prothmann, Sascha; Schwaiger, Benedikt J; Gersing, Alexandra S; Reith, Wolfgang; Niederstadt, Thomas; Felber, Alexandra; Kurre, Wiebke
Abstract : Objectives: Acute Recanalization of Thrombo-Embolic Ischemic Stroke with pREset (ARTESp) is a prospective multicenter study assessing the efficacy and safety of the pREset stent retriever for the treatment of intracranial vessel occlusion. Determination of the effect of transfer status on clinical outcome was a secondary objective. Methods: Efficacy was measured by recanalization success (Thrombolysis in Cerebral Infarction score ≥2b) and favorable clinical outcome at 90 days (modified Rankin Scale 0–2). Intracranial hemorrhage (ICH) and death at 90 days were safety measures. The outcome of directly admitted (DAP) and transferred (TP) patients was investigated using multivariable regression models. Results: Four study centers included 100 patients (mean age 68.3 years, median National Institutes of Health Stroke Scale score 15). Recanalization success was achieved in 84.4% after a mean of 1.7 passes. ICH was detected in 14.0%, with 2.0% being symptomatic. At 90 days, 62.5% of the patients had a favorable outcome and 7.3% died. TP had longer occlusion times (289 vs 180 minutes, p<0.001) and a lower rate of favorable outcome (58.0% vs 78.4%, p=0.046) than DAP. Multivariable regression revealed occlusion time as the critical determinant (OR=0.963, 95% CI 0.931 to 0.997, p=0.032), whereas transfer status itself showed no significant association (OR=0.565, CI 0.133 to 2.393, p=0.438). Conclusions: pREset proved to be safe and effective for the treatment of acute intracranial vessel occlusion. Increased occlusion time impaired clinical outcome in TP. Trial registration number: NCT02437409; Results.